2017
DOI: 10.1016/j.marpolbul.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Mercury accumulation in Lethrinus nebulosus from the marine waters of the Qatar EEZ

Abstract: Total mercury (THg) and methylmercury (MeHg) were recorded in the commercial demersal fish Lethrinus nebulosus, caught from six locations in Qatar EEZ (Exclusive Economic Zone). Concentrations of THg decreased in the order: liver ˃ muscle ˃ gonad. THg concentrations in fish tissue ranged from 0.016 ppm in gonad to 0.855 ppm (mg kg−1 w/w) in liver tissues, while concentrations in muscle tissue ranged from 0.24 to 0.49 ppm (mg kg−1 w/w) among sampling sites. MeHg concentrations were used to validate food web tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Moreover, HM had the highest T-Hg concentrations. This finding is in agreement with previous studies where T-Hg concentrations in HM were found to be the highest and exceeded the guidelines levels in some samples (Elsayed et al, 2020;Al-Ansari et al, 2017;Laird et al, 2017;Ahmad et al, 2016;Burger et al, 2014). HM is a carnivorous predatory fish species that is placed at the top level of the trophic chain (Wei et al, 2018).…”
Section: Fish Contamination Levelssupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, HM had the highest T-Hg concentrations. This finding is in agreement with previous studies where T-Hg concentrations in HM were found to be the highest and exceeded the guidelines levels in some samples (Elsayed et al, 2020;Al-Ansari et al, 2017;Laird et al, 2017;Ahmad et al, 2016;Burger et al, 2014). HM is a carnivorous predatory fish species that is placed at the top level of the trophic chain (Wei et al, 2018).…”
Section: Fish Contamination Levelssupporting
confidence: 93%
“…These variations may be related to the sampled fish (species, age, and size), sampling sites, and season (Da Silva et al, 2020;Elsayed et al, 2020, Wei et al, 2018. Nevertheless, previous studies conducted in the Gulf region reported similar results (Elsayed et al, 2020;Al-Ansari, 2017;Laird et al, 2017;Ahmad et al, 2016;Burger et al, 2014). All of the commercially available fish species in Qatar are considered to have T-Hg levels within acceptable levels set by EU.…”
Section: Fish Contamination Levelsmentioning
confidence: 86%
See 1 more Smart Citation
“…There are numerous physiological and ecological factors that might affect metal contamination and bioaccumulation in the marine environment: geographic location (Frodello and Marchand, 2001;Lewis and Devereux, 2009;Xia et al, 2019;Jarosz-Krzemińska et al, 2020;Lawson et al, 2021), feeding patterns (Azevedo et al, 2020), age and size of species (Mustafa and Guluzar, 2003;Farkas et al, 2003;Le Bourg et al, 2019), sex (Gewurtz et al, 2011;Jankovská et al, 2013), tissue type (Bilandžic et al, 2012;Al-Ansari et al, 2017) and metabolic rates (Caurant et al, 1996;Seco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Arabian Gulf, values of MeHg ranging from 0.112 to 0.865 mg/kg have been reported in tissues of various crustacean species in different locations [19], sometimes exceeding the maximum recommended level of 0.5 mg/kg wet weight [20]. In Qatar, concentrations of MeHg in local commercial fish species, such as Lethrinus nebulosus, were found to range from 0.064 to 0.871 mg/kg [21]. Methylmercury may complex with other chemical groups within the cells leading to DNA damage through free radical formation [22] and also produce chromosomal aberrations [23]: it has indeed been previously recognized as a genotoxic contaminant in aquatic organisms (e.g., [24]).…”
Section: Introductionmentioning
confidence: 99%